(untitled) (Baghdad Science Journal, 2015)
The current study designed to determine the effect of Glucosamine sulfate on the liver tissue of Albino mice .the study included (40)mice divided in to 4 groups(control group had distilled water orally ).The other groups treated with(1000,2000,3000)ml/k .respectively for 8 week .the liver have been taken from dissected animal for microscopic preparation to study the histological changes .Frequently histopathologicale changes appeared in the liver tissue of the exposure groups during (4-8)week .This changes depends on (Dose and Time ). The effects were Congestion ,Infiltration ,Swelling ,Vaculation ,Hyalinization , Amyloid and Necrosis.